Viewing Second Language Acquisition from the Philosophical Perspective of Mindfulness - Huanan Su (Journal of English Language Teaching and Linguistics, 2023)
This current research study attempted to exploratively expose second language learners’ learning acquisition from a philosophical perspective of mindfulness. Regarding this, the researcher deeply studied and identified the behavioral performances of the second language learners in the process of second language acquisition (SLA), which led to the exposure of the close relationship between the theories of philosophy of mindfulness and SLA. As a qualitative research, the current research fully adopted the inductive-deductive method, the comparative analysis method, and the literature review method to deeply analyze the internal relationship between the philosophy of mindfulness and SLA. The research preliminarily found that the cognitive-behavioral theory, under the guidance of the theory of philosophy of mindfulness, provided a good theoretical basis for studying the thinking activities of second language learners’ brains. Thus it is indicated that studies on the operational processes of second language learners’ language cognition should require second language teachers to go deep into all levels of SLA. Consequently, it is suggested that second language teaching should properly follow the scientific laws of cognition and properly develop the potential mindfulness of second language learners, which is an important aspect that all second language teaching experts and teachers can no longer ignore.